Disgust predicts prejudice and discrimination toward individuals with obesity. Issue 6 (16th December 2015) - Vartanian, Lenny R.; Trewartha, Tara; Vanman, Eric J.
Abstract: This study examined the relevance of disgust to evaluations of an obese target person, and the connection between disgust and prejudice toward that person. Participants ( n = 598) viewed an image of an obese or non‐obese woman, and then evaluated that woman on a number of dimensions (emotions, attitudes, stereotypes, desire for social distance). Compared with the non‐obese target, the obese target elicited more disgust, more negative attitudes and stereotypes, and a greater desire for social distance. Furthermore, disgust mediated the effect of the target's body size on all of the outcome variables (attitudes, stereotypes, social distance). Disgust plays an important role in prejudice and discrimination toward individuals with obesity, and might in part explain the pervasiveness of weight bias.